Great expectations - Yamamoto, Mitsu; Dickens, Charles, 1812-1870.; Lynch, Brendan (New York, NY : Baronet Books, 1996)
The orphaned Pip is serving as a blacksmith's apprentice when an unknown benefactor supplies the means for him to be educated in London as a gentleman of "great expectations."
Keywords: Orphans -- Fiction; Young men -- England -- Fiction; England -- Social life and customs -- 19th century -- Fiction